(untitled) (Actualizaciones en Sida e Infectología, 2024)
Spotted fevers are zoonoses caused by bacteria Rickettsia spp. and transmitted by ticks. In the Plata River Basin, on wetlands and banks of rivers and streams, the ticks Amblyomma triste and Amblyomma tigrinum can transmit Rickettsia parkeri, which produces spotted fevers with an acute and benign clinical course. An autochthonous case from Cordoba province is presented, with an etiological diagnosis of Rickettsia parkeri using molecular methods and good clinical evolution.